The Actuator Line Method in the Meteorological LES Model Meso-NH to Analyze the Horns Rev 1 Wind Farm Photo Case - Joulin, Pierre-Antoine; Mayol, Maria Laura; Masson, Valéry; Blondel, Frédéric; Rodier, Quentin; Cathelain, Marie; Lac, Christine (Frontiers in Earth Science, 2020)
The offshore wind market is expected to see massive growth worldwide in the next decade. Recent research in this sector has led to a new generation of wind turbines characterized by larger rotors and higher capacity factors. Furthermore, the trend is to develop larger and denser wind farms which leads to potential deeper interactions with the troposphere. In order to provide an accurate modeling of the processes between the wind turbines, the surface and the atmospheric boundary layer, a new numerical tool has been developed. The ALM has been implemented into the opensource non-hydrostatic mesoscale atmospheric model Meso-NH used in the Large-Eddy Simulation (LES) framework. First, the tool is validated by comparing simulated results with data acquired during the New MEXICO experiments. In particular, good correlation are obtained for normal and tangential loads along the blades and the axial PIV traverse of instantaneous wind velocity components. Once the tool is validated, its ability to reproduce the Horns Rev 1 photo case is evaluated, since it is an emblematic case of wind farm-atmosphere interaction. Simulation output are post-processed using a render algorithm, resulting in synthetic images of cloud radiance. These images show great similarity with the photographs taken. All the results highlight the capacity of this new tool to represent interactions between wind farms and the lower atmosphere with a high level of details.